A phenomenological investigation of coexisting values in healthcare - Stewart, Christopher W., author; Lynham, Susan A., advisor; Coates, Tabitha K. L., committee member; Mumford, Troy V., committee member; Lopes, Tobin P., committee member (Colorado State University. Libraries, 2018)
Health care delivery in the United States has a storied history that has led the American public to expect that their Health Care Practitioners (HCPs) will pursue personal and professional values such as benevolence, equality and capability. A progressive set of events that dates back to the implementation of national health insurance for the elderly and the more recent emergence of events surrounding the implementation of the market-based solution in the Patient Protection and Affordable Care Act have led healthcare organization to become increasingly concerned with the pursuit of market values (e.g. competition; productivity). A review of relevant literature on the coexistence of personal, professional and market values in health care pointed toward a number of potential consequences that might emanate from this coexisting values phenomenon. The HCPs who practice at the nexus of this phenomenon are those who most directly experience such consequences and the aim of this study was to qualitatively explore and illuminate the lived experience of a selection of doctors and nurses. Through an application of a co-constructive approach to inquiry it was found that those HCPs who participated in the study experience professional opportunities to express their personal value preferences, while also experiencing a paradoxical tension when it comes to leaving their patients feeling satisfied with their care experience. It was also found that the HCPs interpret their interactions with the pharmaceutical industry in a variety of ways, and that a HCPs exposure to market values is influenced by their practice area and the type health system they are working in. The vast majority of study participants practice within the same health care organization (system), and it was further found that these HCPs benefit from a quality of leadership and organizational support that enables the pursuit of their care value priorities. Study finding also point to the potential for adverse consequences (e.g. demoralization; burnout) in instances where HCPs are unable to fully realize their personal and professional value priorities. Study implications feature suggestions for practice, theory development and future research, and suggestions for those who might endeavor comparable qualitative research.
Keywords: human values; professional values; healthcare practitioners; values; market values